Impacto de uma intervenção com vídeogame ativo na percepção da imagem corporal e nos comportamentos de compulsão alimentar de adolescentes com excesso de peso - Lins, Nataly Cézar de Lima (2017)
Introduction: adolescence is marked by great susceptibility to risky behaviors, such as inadequate changes in the food pattern that can cause obesity. At this stage there is an increase in concern with physical appearance and social patterns and stigmas lead teenagers to seek a stereotype of beauty, causing increased body dissatisfaction and putting them at risk for the development of eating disorders such as BED. In addition to the physical benefits, the exergames can act in the psychological aspects promoting improvement of the corporal image and of eating disorders. Objective: evaluate the impact of the use of active videogame on self-perception of body image and the development of risk behaviors for binge eating in overweight adolescents. Methods: quasi-experimental study with exergaming intervention, for 50 minutes, 3 times a week, for 8 weeks. Data collection took place between April and December 2016, with 55 adolescents aged 15 to 19 from public schools in Campina Grande, PB. Data were collected through a form for characterization of adolescents, BSQ-34 and ECAP questionnaires, and weight, height and waist circumference were also measured. In SPSS 22.0 Student's t-test and McNemar's test were used to evaluate the effect of the exercise on the studied variables. We adopted a confidence interval of 95%. Results: The majority were female (58.2%), overweight (74.5%), and reported some degree of concern about body image at the beginning of the study (56.4%). This percentage was reduced to 38.2% after the intervention, which also led to a reduction of about eight points in the mean of the self- perception of body image score. Conclusions: Given the positive effects of the intervention, it is emphasized the importance of the implementation of the use of active video game in the childhood and adolescence.